A tradução do conhecimento nas práticas de Promoção da Saúde - Arantes, Bárbara Morais (2014)
Much knowledge has been produced in the area of Health Promotion (HP), but this information is not always translated so that it can be incorporated into everyday practice of health managers and professionals at the local level. The knowledge translation (KT) can contribute to more effective processes in health. The aim of this study was to analyze the effectiveness of KT in the context of health promotion for managers and professionals in public health. The strategies used were literature survey, semi-structured narrative interviews with managers and professionals of a large municipality and documentary analysis of Health Promotion. Content analysis was applied to establish the analytical categories. About the concepts of HP, it was noted that there is still a great confusion with other concepts; the HP actions reported arouse from programs and official publications and the respondents considered any action which was not clinical as being HP; knowledge sources of HP were associated with official documents more than with scientific papers, which were referred only when postgraduate courses were taken; little is known about knowledge translation; the main challenges were related to access and to scientific language, the access to publications of scientific papers has become more available online; among the challenges it is highlighted the great demand for permanent education for managers and professionals. We conclude that the knowledge translation in the context of health promotion takes place most effectively by the primary care team, which by managers; there is still confusion of content and concepts of health promotion with strong linkages to prevention and education health; promotion practices are associated to those induced by public policies and programs predominantly from official documents and manuals from the Ministry of Health, principal source used by managers and professionals, access to new knowledge was associated with the academic world by internet, official sources by the documents and manuals, on the processes of knowledge translation most important were collective activities such as workshops and reading group, among these challenges include the difficulty of access to restricted sites and / or paid on the Internet, setting up spaces for discussion and exchange of experiences.